Water knot: Case report of a rare complication during a urodynamic test. (November 2021) - Blas, Leandro; Roberti, Javier; Lopez, Francisco; Ameri, Carlos Alberto
Intravesical catheter knotting is a rarely reported event that could lead to serious complications. We present a case that occurred during urodynamic test with two K30 tubes: a 56-year-old female with a double knot of two K30 (8.4 Fr) tubes. This case was resolved by removing the catheters with sustained traction. Because catheter knotting can be a serious complication, we recommend the use of a double-lumen catheter when possible and assessment of a safe insertion length.